2016
DOI: 10.11118/actaun201664020395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LDL Addition Into Selected Bull Sperm Diluters on Resistance of Spermatozoa Against Cold Shock

Abstract: The aim of work was to determine the effect of LDL cholesterol addition into selected diluters on the resistance of spermatozoa against cold shock and on their short-term survivability during cold test. The hypothesis was that the addition of LDL cholesterol will positively affects sperm resistance to cold shock and ensures a higher survivability of spermatozoa during short-term cold survival test. Four bulls of different breeds and ages, from the same sire insemination center were used. A total of eight semen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…1). This is contrary to LDL effect before cryopreservation on PM assessed by our previous study (Beran et al, 2016) and other studies e. g. (Hu et al, 2011), which revealed its significant effect on PM but also after thawing. Above all, our results are in compliance with a study (Amirat et al, 2005) where the authors provided the closest insight using scanning electron microscopy into the LDL function in PM.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…1). This is contrary to LDL effect before cryopreservation on PM assessed by our previous study (Beran et al, 2016) and other studies e. g. (Hu et al, 2011), which revealed its significant effect on PM but also after thawing. Above all, our results are in compliance with a study (Amirat et al, 2005) where the authors provided the closest insight using scanning electron microscopy into the LDL function in PM.…”
Section: Discussioncontrasting
confidence: 99%
“…1) crucial for successful binding and fertilization of oocytes (Layek et al, 2016). Importantly, the same concentration of LDL in the same extender was confirmed as significantly favourable for PM integrity after collection (Beran et al, 2016). This is supported by evidence that LDL had a positive indirect influence on maintaining the functional status of PM due to its high binding affinity to BSP proteins (Lusignan et al, 2011), thereby preventing destabilization (Srivastava et al, 2013).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations